2018
DOI: 10.1093/imrn/rny258
|View full text |Cite
|
Sign up to set email alerts
|

Highest Weights for Categorical Representations

Abstract: We present a criterion for establishing Morita equivalence of monoidal categories, and apply it to the categorical representation theory of reductive groups G. We show that the "de Rham group algebra" DpGq (the monoidal category of D-modules on G) is Morita equivalent to the universal Hecke category DpN zG{N q and to its monodromic variant r DpBzG{Bq. In other words, de Rham G-categories, i.e., module categories for DpGq, satisfy a "highest weight theorem" -they all appear in the decomposition of the universal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 4 publications
1
4
0
Order By: Relevance
“…Informally, the theorem allows one to reconstruct a piece of the entire module from its K invariants, which are often easier to analyze directly. The result and its proof are similar to work of Ben-Zvi-Gunningham-Orem [BZGO18]; for a generalization see also the interesting paper of Yang [Yan21].…”
Section: Hecke Algebras and Invariant Vectorssupporting
confidence: 73%
“…Informally, the theorem allows one to reconstruct a piece of the entire module from its K invariants, which are often easier to analyze directly. The result and its proof are similar to work of Ben-Zvi-Gunningham-Orem [BZGO18]; for a generalization see also the interesting paper of Yang [Yan21].…”
Section: Hecke Algebras and Invariant Vectorssupporting
confidence: 73%
“…We do not formulate the result in these terms. The assertion stated here follows from our Theorem 3.0.1 using the methods of[BZGO18].…”
mentioning
confidence: 67%
“…4.5.4. We would also like to mention, for a reductive group G, a nice analogue of highest weight theory in the present setting due to Ben-Zvi-Gunningham-Orem [BZGO18]. Namely, they showed that, for any maximal unipotent subgroup N , an arbitrary D-mod(G) representation C can be reconstructed from its N -invariants, or even the weak Cartan invariants of the latter…”
Section: Let Us Mention a Few Features And Examplesmentioning
confidence: 81%
“…Remark 4.5.5. The argument of [BZGO18] yields the following useful variation. Given any subgroup H of a group K such that the quotient of K by the normalizer of H is proper, the tautological map…”
Section: Let Us Mention a Few Features And Examplesmentioning
confidence: 99%